Legal Effectiveness of E-Litigation Implementation on Case Settlement: Evidence from the Malang City Religious Court - Supriadi; M. Muhibbin; Suratman (APPTHI, 2025)
This study discusses the effectiveness of the implementation of Supreme Court Regulation Number 1 of 2019, as amended by Supreme Court Regulation Number 7 of 2022, concerning Case Administration and Trials in Courts Electronically (e-Litigation). The research focuses on case settlement at the Malang City Religious Court. Using an empirical juridical approach, this study examines the implementation of e-Litigation before and after the regulatory changes, along with the obstacles encountered and efforts made for improvement. The findings indicate that the implementation of e-Litigation has had a positive impact by simplifying processes, improving time efficiency, reducing litigation costs, and enhancing transparency. However, challenges such as limited public understanding of digital systems, inadequate infrastructure, and legal cultural barriers still hinder full effectiveness. Based on the theory of legal effectiveness, the implementation of e-Litigation in Malang City shows a promising direction of development, although it is not yet fully optimal. Strengthening public education, increasing digital legal literacy, and adapting community legal culture are necessary to ensure that the system can operate more efficiently and accountably.